2021
DOI: 10.1029/2020wr029038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tide‐Induced Unstable Flow on Seawater Intrusion and Submarine Groundwater Discharge

Abstract: Groundwater is a valuable source of freshwater in coastal areas. The groundwater flux in coastal aquifers generally occurs in two processes: seawater intrusion (SWI) and submarine groundwater discharge (SGD) (Robinson et al., 2018). SWI, the subsurface movement of seawater into freshwater aquifers, is a natural phenomenon in coastal areas (Werner et al., 2013). The hydraulic head difference caused by the density difference between seawater and freshwater drives the landward movement of seawater, thus forming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 47 publications
4
26
0
Order By: Relevance
“…For example, Q f efflux in the seasonal case with a tidal amplitude of 1.85 cm exhibited high-frequency fluctuations within the intervals of 109-142 min and 752-971 min (unstable stage). Just as previous studies suggested (Fang et al, 2021;Greskowiak, 2014;Röper et al, 2015), the Q f efflux fluctuated over time under the unstable regime, which was also observed in the fixed case (unstable USP) with a tidal amplitude of 2.2 cm and inland freshwater input of 0.271 m 3 /d/m. Fixed cases presented an increased fluctuation amplitude of the Q f efflux over time as the tidal amplitude increased or the inland freshwater input decreased.…”
Section: Variations In Fluxes Across the Aquifer-sea Interface Under ...supporting
confidence: 72%
See 1 more Smart Citation
“…For example, Q f efflux in the seasonal case with a tidal amplitude of 1.85 cm exhibited high-frequency fluctuations within the intervals of 109-142 min and 752-971 min (unstable stage). Just as previous studies suggested (Fang et al, 2021;Greskowiak, 2014;Röper et al, 2015), the Q f efflux fluctuated over time under the unstable regime, which was also observed in the fixed case (unstable USP) with a tidal amplitude of 2.2 cm and inland freshwater input of 0.271 m 3 /d/m. Fixed cases presented an increased fluctuation amplitude of the Q f efflux over time as the tidal amplitude increased or the inland freshwater input decreased.…”
Section: Variations In Fluxes Across the Aquifer-sea Interface Under ...supporting
confidence: 72%
“…In other words, tide‐induced unstable flow is a natural phenomenon in coastal aquifers. Under the unstable USP situation, the extent of SWI, total SGD, and its components would vary obviously over time, which is significantly different from those observed under a stable situation (Fang et al., 2021; Greskowiak, 2014; Röper et al., 2015).…”
Section: Introductionmentioning
confidence: 79%
“…The most common practice in such studies is to run a steady‐state simulation of the studied area, with the model parameters adapted to match the modeled steady state to the observed average state of the aquifer. The output of the calibrated steady‐state model is applied as initial conditions for transient simulations (which may or may not include cyclical processes), which are used to constrain the dominant factors that control the hydrologic functioning of a given system (Fang et al., 2021; Levanon et al., 2016; Oz et al., 2015; Paldor et al., 2019). Transient simulations are also used to assess vulnerability to various environmental changes (e.g., sea‐level rise, recharge intensification), and to predict future trends in the hydrologic regime (Guimond & Michael, 2021; Masterson et al., 2014; Paldor & Michael, 2021; Xiao et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory experiments of Fang et al. (2021) and Röper et al. (2015) captured the salt finger movement in the intertidal region.…”
Section: Introductionmentioning
confidence: 99%